Structuring Lexical Data and Digitising Dictionaries : Grammatical Theory, Language Processing and Databases in Historical Linguistics - Arista, Javier Martín,; López, Ana Elvira Ojanguren, (Language and Computers., 2024)
In order to guarantee open access and full searchability, research in historical lexicography and lexicology must follow the same directions as the evolution of the Internet, which has moved from hypertext-based resources to more significative s